Penerapan Metode Total Physical Response (TPR) dalam Meningkatkan Pemahaman Kosakata Bahasa Arab Mahasiswi IDIA - Nanda Ramadani (Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
Learning arabic as a foreign language is not an easy thing, with the problem of learning Arabic for student who have just leaned Arabic, it certainly makes students feel that is diffucul to learn it while they are required to use Arabic in communication in theur daily life at IDIA intensive prenduan daugther. Based on data from prelimunary observations/preliminary studies, information is obtained that the learning process of vocabulary (Mufrodat) in IDIA prenduan is less effective. Most of the students complained when the teacher ordered them to memorize some vocabulary related to the theme that will be taught that day. Meanwhile, based on interviews with students that the learning process is still insignificant, they still have difficulty memorizing vocabulary and understanding the material and still have difficulty writing in this case the dictation, from this statement it is necessary to have a breakthrough in the Arabic language learning approach. In this study, this study aims to (1) describe the application of the Total Physica Response (TPR) method in learing Arabic. This study aims to (1) describe the application of the Total Physical response (TPR) method in learning Arabic vocabulary for student of class 1 B IDIA intensive femele prenduan, and (2) describe the increase in understanding of Arabic vocabulary for student of class 1 B IDIA intensive femele prenduan through the application of the Total Physical Response (TPR) method.